Explaining the consequences of missed nursing care from the perspective of nurses: a qualitative descriptive study in Iran - Maryam Janatolmakan; Alireza Khatony (BMC, 2022)
Abstract Background Missed nursing care is a global challenge that can have many consequences. Knowing the experiences of clinical nurses can be helpful. Therefore, this study was conducted to explain the experiences of Iranian nurses regarding the consequences of missed nursing care. Methods This qualitative descriptive study was conducted with a content analysis approach. Sampling was done by the purposeful sampling method and continued until data saturation. Data were collected by in-depth semi-structured interviews. Data were analyzed using qualitative content analysis and Graneheim and Lundman's method. MAXQDA version 10 software was used for data management. Results The participants included 14 nurses with a mean age of 38.7 ± 7.7 years. The data were classified into three categories: patient-related outcomes, nurse-related outcomes, and organization-related outcomes. These categories included nine subcategories entitled "moral distress", "job dissatisfaction", " decreased quality of nursing care "," patient dissatisfaction ","adverse events"," absenteeism ","intention to leave and subsequent turnover", "decreased hospital credit", and "increased hospital costs". Conclusion Missed nursing care can have adverse consequences for the patients, nurses, and organizations. Therefore, it is necessary to adopt management strategies such as providing sufficient manpower and increasing nurses' job satisfaction to reduce the amount of missed nursing care. Further studies are needed to explain the predictors of the missed nursing care consequences.